Macroprolactinemia: a mini-review and update on clinical practice - Katherine Koniares, M.D; Claudio Benadiva, M.D; Lawrence Engmann, M.D; John Nulsen, M.D; Daniel Grow, M.D (Elsevier, 2023)
Hyperprolactinemia is common among infertile patients, with up to 15%-20% of women with oligomenorrhea having hyperprolactinemia. Suppression of the hypothalamic-pituitary-gonadal axis via inhibition of pulsatile gonadotropin releasing hormone because of hyperprolactinemia is a common endocrine etiology of infertility. There are 3 forms of human prolactin (PRL): monomeric PRL, dimeric PRL, and macro-PRL. Also known as big-big PRL, macro-PRL has a molecular weight >150 kDa and normally comprises 5%-10% of circulating PRL. When the predominant form of circulating PRL is macro-PRL, macroprolactinemia is diagnosed. Among patients with hyperprolactinemia, 10%-46% have macroprolactinemia. Patients with macroprolactinemia are at risk of unnecessary pituitary imaging and treatment with dopamine agonists if not correctly diagnosed. Given the high prevalence of macroprolactinemia among patients with elevated PRL levels and the different management of patients with macroprolactinemia vs true monomeric hyperprolactinemia, all patients with persistently elevated PRL levels should be screened for macro-PRL.